Impacts of a Large-Scale Parenting Program: Experimental Evidence from Chile - Carneiro, Pedro; Galasso, Emanuela; Garcia, Italo Lopez; Bedregal, Paula; Cordero, Miguel (Journal of Political Economy, 2024)
We present results from a large-scale experimental evaluation of a national parenting program in Chile. The program is low cost: it lasts only 6–8 weeks, and it is administered to groups of eight to 12 parents. It is implemented by the national health system, taking advantage of its existing physical infrastructure and human resources. We find that 3 years after the interventions ends, children whose parents are offered the opportunity to participate in this program increase their vocabulary and socioemotional development scores by 0.1 standard deviations, mirrored by similar improvements in caregiver’s parenting behaviors and beliefs.